Friction Stir Welding and Processing in Alloy Manufacturing - de Saracibar, Carlos Agelet (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Friction stir welding (FSW) is considered to be the most significant development in metal joining in decades and, in addition, is a ""green"" technology due to its energy efficiency, environmental friendliness, and versatility. This process offers a number of advantages over conventional joining processes. Furthermore, because welding occurs via the deformation of material at temperatures below the melting temperature, many problems commonly associated with joining of dissimilar alloys can be avoided, and thus, high-quality welds are produced. Due to this fact, FSW has been widely used in different industrial applications where metallurgical characteristics should be retained, such as in the aeronautic, naval, and automotive industries.